2016
DOI: 10.7454/nrjs.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Success Rate of Kasai Portoenterostomy

Abstract: Introduction. Surgical repositioning of biliary drainage to the intestine (jejunum) through an artificial fistula (portoenterostomy) following surgical removal of extrahepatic residual biliary duct in biliary atresia, which is first proposed by Kasai has never been evaluated in our center. Thus, we run a study aimed to find out the success rate. Method. We run a cohort study retrospectively enrolled subjects with biliary atresia consecutively. A review of histopathology was carried out, and focused on degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…12 Operative therapy with KPE is still chosen with a success rate that depends on the degree of fibrosis process of the liver which is an advanced process of biliary atresia. 13 A study in Indonesia showed the success of KPE was 51.7%. 14 Meanwhile, another study examined the outcome of patients who underwent KPE and found that the mortality rate was 58.5% with the main causes being sepsis and liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…12 Operative therapy with KPE is still chosen with a success rate that depends on the degree of fibrosis process of the liver which is an advanced process of biliary atresia. 13 A study in Indonesia showed the success of KPE was 51.7%. 14 Meanwhile, another study examined the outcome of patients who underwent KPE and found that the mortality rate was 58.5% with the main causes being sepsis and liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies in findings may result from differences between antibiotics regimens and duration. Additionally, several factors have been mentioned to affect the success rate of Kasai HPE: early age (before 7th week of life), ductal plate malformation, postoperative steroid, prevention of cholangitis, and the degree of fibrosis (29)(30)(31)(32). The latter has been associated with serum IL-8 and IL-6 indicating inflammation and predicting fibrosis (33), while a shorter Roux-loop length in Kasai HPE had a similar efficacy as the conventional length (34).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported by Sastiono et al . [16] that the success rate was 33.3% in those operated on below the age of 90 days. Another study by Schoen et al .…”
Section: Discussionmentioning
confidence: 99%